Corruption and human rights law in Africa - Olaniyan, Kolawole (Oxford ; Portland, Oregon : Hart Publishing, 2016)
This book provides a framework for complementarity between promoting and protecting human rights and combating corruption. The book makes three major points regarding the relationship between corruption and human rights law. First, corruption per se is a human rights violation, insofar as it interferes with the rights of the people to dispose of their natural wealth and resources and thereby increases poverty and frustrates socio-economic development. Second, corruption leads to a multitude of human rights violations. Third, the book demonstrates that human rights mechanisms have the capacity to provide more effective remedies to victims of corruption than can other criminal and civil legal mechanisms.
Corruption and human rights law : historical and conceptual frameworks -- The international dimensions of corruption and money laundering -- National legal frameworks for fighting corruption in Africa -- International legal frameworks for fighting corruption across Africa -- Effects of corruption on human and peoples' rights -- The potential of human rights law in combating corruption in Africa -- Conclusions.
Includes bibliographical references (pages 373-381) and index.
Keywords: Corruption -- Law and legislation -- Africa; Human rights -- Africa; Human rights; Corruption -- Law and legislation; Africa